2020
DOI: 10.3390/molecules25153451
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal and Anti-Inflammatory Properties of The Essential Oils Obtained from Monoecious, Male, and Female Inflorescences of Hemp (Cannabis sativa L.) and Their Encapsulation in Nanoemulsions

Abstract: Among the various innovative products obtainable from hemp (Cannabis sativa L.) waste biomass originating from different industrial processes, the essential oil (EO) deserves special attention in order to understand its possible application in different fields, such as cosmetics, pharmaceuticals, and botanical insecticides. For the purpose, in the present work, we studied the chemical composition of EOs obtained from different hemp varieties, namely Felina 32 and Carmagnola Selezionata (CS) using monoecious, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
3
21
1
Order By: Relevance
“…As for HaCat cells, their viability seems affected by the exposure to the water extract when exposed to high concentrations (300 and 500 ”g/mL) and longer experimental times (72 h) ( Figure 4 B). These findings are in line with recent literature in which the same cell line was treated with essential oil from female inflorescence [ 32 ]. Again, when cell proliferation is affected by H 2 O 2 administration, the exposure to hemp extract at concentration up to 100 ”g/mL exerted a protective effect both at 24 and 48 h.…”
Section: Resultssupporting
confidence: 92%
“…As for HaCat cells, their viability seems affected by the exposure to the water extract when exposed to high concentrations (300 and 500 ”g/mL) and longer experimental times (72 h) ( Figure 4 B). These findings are in line with recent literature in which the same cell line was treated with essential oil from female inflorescence [ 32 ]. Again, when cell proliferation is affected by H 2 O 2 administration, the exposure to hemp extract at concentration up to 100 ”g/mL exerted a protective effect both at 24 and 48 h.…”
Section: Resultssupporting
confidence: 92%
“…The authors attributed this effect to the role of Lavandula angustifolia EO on the stimulation of TGF-ÎČ1, an important regulatory factor in reproduction fibroblasts which is involved in the formation of granular tissue as well as in the synthesis and accumulation of collagen fibers [ 167 ]. EOs-loaded nanoemulsions have also been studied for their potential anti-inflammatory activity by in vitro and in vivo (in zebrafish) assays [ 39 , 168 ]. In particular, Borges et al focused on the anti-inflammatory activity of nanoemulsions loaded with Rosmarinus officinalis L. EO, exploiting two parameters: the cellular antioxidant activity (CAA) and the nitric oxide (NO∙) production.…”
Section: Eos Encapsulation Strategies In Drug Delivery Systemsmentioning
confidence: 99%
“…Therefore, authors concluded that the produced nanoemulsions was able to enhance the anti-inflammatory effect of EO, further reducing the production of NO∙. In particular, the potential pro- or anti-inflammatory effect of EO was investigated on human keratinocytes and fibroblasts, in order to evaluate their safe use for operators [ 168 ]. Herein, Rossi et al, as well as proving that EOs present a strong toxicity against larvae and pupae of the main malaria vectors An.…”
Section: Eos Encapsulation Strategies In Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the reduced size of the droplets of the internal phase and the consequent increment of the surface area, NEs allow a better interaction of the encapsulated compounds into the target site [ 23 ] by overcoming the EO’s poor physicochemical stability and solubility issues [ 24 ]. This strategy can boost the applicability of EOs as natural insecticides [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%